Construção de um forno tubular rotativo utilizando lâmpadas halógenas para a síntese de nanopartículas - Carvalho, Joelma Anastácio (2011)
This paper deals with the study, construction and testing of a rotary tube furnace for calcinations and obtaining metal oxides from the conventional sol-gel protein process. The research approach aims to increase energy efficiency in order to reduce the expenditure of energy and time to obtain nanoparticles, using 6 (six) bilateral basis tungsten halogen lamps with 1000W/220V each one. This furnace is able to perform synthesis with good mixing by rotation of the powder during calcination with the differential use of halogen lamps, which enables a high heating and cooling of the sample. The components were able to withstand high temperatures, equipped with hard oxidation, and the efficient thermal insulation by low thermal conductivity in order to obtain low heat loss through the walls of the oven. The assembly process was marked by several improvements over the original design, since the beginning, the oven did not have the cooling system and its use has improved efficiency and conservation of halogen lamps. The research results show the better efficiency of the furnace of halogen lamps in comparison to the resistance furnace on the particle size and its homogeneity, as well as the loss of heat. In this last item reaching a better yield around 50% compared to electric resistance furnace.